2014
DOI: 10.1016/j.pain.2013.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Single intrathecal administration of the transcription factor decoy AYX1 prevents acute and chronic pain after incisional, inflammatory, or neuropathic injury

Abstract: The persistence of pain after surgery increases the recovery interval from surgery to a normal quality of life. AYX1 is a DNA-decoy drug candidate designed to prevent post-surgical pain following a single intrathecal injection. Tissue injury causes a transient activation of the transcription factor EGR1 in the dorsal root ganglia-dorsal horn network, which then triggers changes in gene expression that induce neuronal hypersensitivity. AYX1 is a potent, specific inhibitor of EGR1 activity that mimics the genomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 33 publications
4
47
0
Order By: Relevance
“…In the current study, single prolonged stress (SPS) was employed to further analyze these effects on PTSD192021. Complete Freund’s adjuvant (CFA) injection was used to promote chronic inflammatory pain22. Minocycline was used to inactivate microglia and c -fos antisense oligodeoxynucleotides (ASO) was used to disable activated neurons2324.…”
mentioning
confidence: 99%
“…In the current study, single prolonged stress (SPS) was employed to further analyze these effects on PTSD192021. Complete Freund’s adjuvant (CFA) injection was used to promote chronic inflammatory pain22. Minocycline was used to inactivate microglia and c -fos antisense oligodeoxynucleotides (ASO) was used to disable activated neurons2324.…”
mentioning
confidence: 99%
“…23 More recently, preclinical investigations of the DNA transcription factor decoy, AYX1, demonstrated improved weight-bearing and spontaneous rearing in a rat knee surgery model. 24 The strengths of our study design are that it was a comprehensive comparison between a triple nonopioid analgesic combination and all three of its respective double-drug combinations included a systematic assessment of pain at rest as well as pain evoked by movement. However, this study is also limited by incomplete recruitment as well as concomitant patient-controlled opioid administration, which may equalise appreciable differences in efficacy of the four studied treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that there is activation of peripheral and central gliocytes complicated with release of inflammatory cytokines in neuropathic pain. This uncovered important mechanism for the pathogenesis of neuropathic pain and the accompanied symptoms [19][20][21][22], and it also revealed an important therapeutic target for the treatment of neuropathic pain [23][24][25].…”
Section: Cell Biochem Biophysmentioning
confidence: 92%